Tenofovir‐based alternate therapies for chronic hepatitis B patients with partial virological response to entecavir. Issue 8 (24th November 2014) - Lu, L.; Yip, B.; Trinh, H.; Pan, C. Q.; Han, S.‐H. B.; Wong, C. C.; Li, J.; Chan, S.; Krishnan, G.; Wong, C. C.; Nguyen, M. H.
Summary Entecavir (ETV) is a first‐line antiviral therapy for treating chronic hepatitis B (CHB); however, some patients have suboptimal response to ETV. Currently, there are limited data on how to approach these patients. Therefore, our aim was to compare the effectiveness of two alternate therapies – tenofovir (TDF) monotherapy and combination therapy of ETV+TDF – in CHB patients with ETV partial virological response. We conducted a retrospective study of 68 patients who had partial virological response to ETV, defined as having detectable HBV DNA following at least 12 months of ETV, and were switched to TDF monotherapy (n = 25) or ETV+TDF (n = 43). Patients were seen in seven US liver/community‐based clinics and started on ETV between 2005 and 2009. The majority of patients were male; the vast majority were Asian and had positive hepatitis B e antigen (HBeAg). Patients in both groups had similar pretreatment characteristics. Complete viral suppression (CVS) rates with TDF monotherapy and ETV+TDF were similar after 6 months (71% vs 83%, P = 0.23) and 12 months (86% vs 84%, P = 0.85), and there was no statistically significant difference in CVS rates even when only patients with higher HBV DNA levels at switch (>1000 IU/mL) were evaluated. Multivariate analysis indicated that ETV+TDF was not an independent predictor of CVS compared to TDF monotherapy (OR = 1.19, P = 0.63). In conclusion, TDF monotherapy and ETV+TDF are comparable in achieving CVS in CHB patients with partial virological response to ETV. Long‐term alternate therapy with one pill (TDF monotherapy) vs two pills (ETV+TDF) could lead to lower nonadherence rates and better treatment outcomes.